1999
DOI: 10.1002/(sici)1097-4636(1999)48:4<417::aid-jbm4>3.0.co;2-x
|View full text |Cite
|
Sign up to set email alerts
|

Disaggregated osteoclasts increase in resorption activity in response to roughness of bone surface

Abstract: The roughness of the bone matrix surface affects osteoblastic differentiation. However, the effect of the roughness of the matrix surface on osteoclastic bone resorption remains to be studied. We examined the latter effect using disaggregated osteoclasts from neonatal rats. The resorption pit number and the total pit area on the rough surface were not different from those on smooth surfaces after 1 day, but they were 2 or more times higher after 3 days. The number of osteoclasts was not different on bone slice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 20 publications
1
9
1
Order By: Relevance
“…7). Both samples showed resorption pits comparable to those detected by other investigators16, 24, 38, 39, 41 The resorption pits on the bone appeared characteristically scallop‐shaped, with long meandering trails, attributed to the movement of the osteoclast whilst resorbing. The resorption pits on the SBF‐HA showed two parts, apparent apatite crystals in the centre of the pit, whilst the edge remains sharp and dense.…”
Section: Discussionsupporting
confidence: 82%
“…7). Both samples showed resorption pits comparable to those detected by other investigators16, 24, 38, 39, 41 The resorption pits on the bone appeared characteristically scallop‐shaped, with long meandering trails, attributed to the movement of the osteoclast whilst resorbing. The resorption pits on the SBF‐HA showed two parts, apparent apatite crystals in the centre of the pit, whilst the edge remains sharp and dense.…”
Section: Discussionsupporting
confidence: 82%
“…In an in vivo study performed in a canine total hip arthroplasty model,18 the bone tissue apposition on a corundum‐blasted titanium alloy was higher on smoother surfaces ( R a from 2.9 to 6.7 μm). Moreover, the release of titanium into the culture medium was lower for the smoother samples,24 and the resorption of bovine cortical bone by osteoclasts in cultures derived from rat long bones was lower on smoother bone slices 26…”
Section: Discussionmentioning
confidence: 99%
“…The biocompatibility of artificial materials designed for or used in hard tissue surgery usually has been tested in terms of their interactions with osteoblasts and osteoclasts6, 14–18, 20–28 but more rarely with soft‐tissue cells present in the bone or in close proximity to the bone, such as fibroblasts17, 19, 29 or vascular cells, including endothelium, pericytes, and smooth muscle cells 30–33. In titanium‐coated bone implants, a vascular network has been seen in the grooves on the material surface, that is, in the interface between the implant and the newly formed bone 32.…”
Section: Introductionmentioning
confidence: 99%
“…Geblinger et al [ 30 32 ] reported an increased half-life of the actin rings of resorbing RAW 264.7 osteoclast-like cells on rough artificial calcium substrates compared to smooth ones (roughness in the nanometer range), which could explain our observed tendency for higher resorption on the rough surfaces, as well as a very high dynamics of the sealing-zone being locally regulated by surface roughness. However, topography-dependent higher resorption on rougher surfaces is described in the literature in osteoclast-like cell lines and osteoclasts generated from bone marrow [ 33 36 ]. Nevertheless, the effects in cultures of primary osteoclasts may be due to the presence of osteoblastic cells or stromal cells, which are well known to strongly affect osteoclastic behavior [ 34 ].…”
Section: Discussionmentioning
confidence: 99%